May the Road Rise Up to Meet You : a Novel - Troy, Peter (New York : Doubleday, 2012)
"An engrossing, epic American drama told from four distinct perspectives, spanning the first major wave of Irish immigration to New York through the end of the Civil War. Four unique voices; two parallel love stories; one sweeping novel rich in the history of nineteenth century America. This remarkable debut draws from the great themes of literature--famine, war, love, and family--as it introduces four unforgettable characters. Ethan McOwen is an Irish immigrant whose endurance is tested in Brooklyn and the Five Points at the height of its urban destitution; he is among the first to join the famed Irish Brigade and becomes a celebrated war photographer. Marcella, a society girl from Spain, defies her father to become a passionate abolitionist. Mary and Micah are slaves of varying circumstances, who form an instant connection and embark on a tumultuous path to freedom. All four lives unfold in two beautiful love stories, which eventually collide. Written in gorgeous language that subtly captures the diverse backgrounds of each character and interspersed with letters, journals, and dreams, this unforgettable story, rendered in cinematic detail, is about having faith in life's great meaning amidst its various tangles"--Provided by publisher.
Keywords: United States -- Fiction -- History -- 19th century; Historical fiction